2018
DOI: 10.1111/jcmm.14092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of myo‐inositol trispyrophosphate (ITPP) on tumour oxygenation and response to irradiation in rodent tumour models

Abstract: Tumour hypoxia is a well‐established factor of resistance in radiation therapy (RT). Myo ‐inositol trispyrophosphate (ITPP) is an allosteric effector that reduces the oxygen‐binding affinity of haemoglobin and facilitates the release of oxygen by red blood cells. We investigated herein the oxygenation effect of ITPP in six tumour models and its radiosensitizing effect in two of these models. The evolution of tumour pO 2 upon ITPP administration was monitored on six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Our study results are similar to those obtained by Tran et al [ 33 ], who measured pO 2 in six murine and two rat tumor models, and demonstrated an increase in tumor pO 2 by 7–10 mm Hg for up 72–96 h with slightly different ITPP protocols. They also demonstrated radiosensitization to single-dose radiation, similar to Grgic et al, who demonstrated increased DNA damage after ITPP and radiation [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study results are similar to those obtained by Tran et al [ 33 ], who measured pO 2 in six murine and two rat tumor models, and demonstrated an increase in tumor pO 2 by 7–10 mm Hg for up 72–96 h with slightly different ITPP protocols. They also demonstrated radiosensitization to single-dose radiation, similar to Grgic et al, who demonstrated increased DNA damage after ITPP and radiation [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…A relatively rich vascular network is present in young tumors, deteriorating quickly with tumor growth. Even though pO 2 in young 4T1 tumors may be high ( Fig 2 ), it declines rapidly, rendering the tumors hypoxic [ 33 , 41 ]. The ITPP dosing frequency needs to be adjusted to tumor growth rate, with shorter intervals in fast-growing tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy to increase the oxygen delivery without altering the perfusion is to promote the release of oxygen by hemoglobin (Hb). It has been shown that allosteric effectors (such as efaproxiral or myo-inositol trispyrophosphate) binding to Hb results in a decreased hemoglobin-oxygen (Hb-O 2 ) affinity and an increased tumor oxygenation (Teicher et al, 1998;Khandelwal et al, 1999;Amorino et al, 2001;Hou et al, 2004;Hou et al, 2005;Suh et al, 2006;Hou et al, 2007;Scott et al, 2007;Aprahamian et al, 2011;Limani et al, 2016;Tran et al, 2019;Cao-Pham et al, 2020). The increases in regulated oxygen-releasing capacity of red blood cells has been shown to potentiate the response to irradiation (Teicher et al, 1998;Khandelwal et al, 1999;Amorino et al, 2001;Suh et al, 2006;Hou et al, 2007;Scott et al, 2007;Tran et al, 2019).…”
Section: Decreasing Tumor Hypoxia By Improving the Oxygen Deliverymentioning
confidence: 99%
“…It has been shown that allosteric effectors (such as efaproxiral or myo-inositol trispyrophosphate) binding to Hb results in a decreased hemoglobin-oxygen (Hb-O 2 ) affinity and an increased tumor oxygenation (Teicher et al, 1998;Khandelwal et al, 1999;Amorino et al, 2001;Hou et al, 2004;Hou et al, 2005;Suh et al, 2006;Hou et al, 2007;Scott et al, 2007;Aprahamian et al, 2011;Limani et al, 2016;Tran et al, 2019;Cao-Pham et al, 2020). The increases in regulated oxygen-releasing capacity of red blood cells has been shown to potentiate the response to irradiation (Teicher et al, 1998;Khandelwal et al, 1999;Amorino et al, 2001;Suh et al, 2006;Hou et al, 2007;Scott et al, 2007;Tran et al, 2019). It has been suggested that the beneficial aspect of allosteric effectors could also be mediated by the suppression of HIF-1α and to down-regulation of HIFinducible genes such as VEGF (Aprahamian et al, 2011).…”
Section: Decreasing Tumor Hypoxia By Improving the Oxygen Deliverymentioning
confidence: 99%